2013
DOI: 10.5935/abc.20130205
|View full text |Cite
|
Sign up to set email alerts
|

Is Conventional Cardiac Pacing Harmful in Patients with Normal Ventricular Function?

Abstract: BackgroundRight ventricular pacing may be deleterious in patients with left ventricular dysfunction, but in patients with normal function the impact of this stimulation triggering clinically relevant ventricular dysfunction is not fully established.ObjectivesTo evaluate the clinical, echocardiographic findings of patients with previously normal left ventricular function underwent implantation of a pacemaker.MethodsObservational, cross-sectional study with 20 patients, who underwent implantation of pacemaker, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…The LV pre-ejection time, for instance, assessed in the present study, is useful to quantify intraventricular dyssynchrony with good reproducibility according to previous studies, such as the CARE-HF study 21 . Recently, Sá et al 22 observed the prolonging of this measurement in a small group of patients, who were also Chagasic with normal LVEF, throughout an eight-month period. The authors observed that although the LVPET measurements did not reach the cutoff required for the diagnosis of VD (≥ 140 ms), this was the only assessed VD measure that showed increases throughout follow-up.…”
Section: Left Ventricular Pre-ejection Timementioning
confidence: 87%
“…The LV pre-ejection time, for instance, assessed in the present study, is useful to quantify intraventricular dyssynchrony with good reproducibility according to previous studies, such as the CARE-HF study 21 . Recently, Sá et al 22 observed the prolonging of this measurement in a small group of patients, who were also Chagasic with normal LVEF, throughout an eight-month period. The authors observed that although the LVPET measurements did not reach the cutoff required for the diagnosis of VD (≥ 140 ms), this was the only assessed VD measure that showed increases throughout follow-up.…”
Section: Left Ventricular Pre-ejection Timementioning
confidence: 87%
“…W dotychczasowych doniesieniach na ten temat można spotkać rozbieżności w odniesieniu do różnych urządzeń. Niektóre badania potwierdzają poprawę stanu psychicznego chorych po implantacji PM [10,14], natomiast inne przedstawiają odmienne wyniki [15]. Rozbieżności występują również w ocenie chorych po implantacji ICD i CRT.…”
Section: Dyskusjaunclassified
“…The MOST study showed that the patients with baseline lower ejection fraction (EF), history of myocardial infarction, and a worse New York Heart Association (NYHA) functional class are more likely to have these adverse events 2 . Batista and his colleagues have shown that even in patients with normal baseline ventricular function, conventional RV apical pacing leads to change in functional class, worsening in walk test, increased B type natriuretic peptide levels at the end of 2 years 5 . Over time, the sequelae of chronic pacing from the RV apex are a higher risk of development of left ventricular dysfunction, heart failure, AF, and death 6, 7, 8, 9.…”
Section: Adverse Effects Of Rv Apical Pacingmentioning
confidence: 99%